ANALYSIS OF EXPOSURE OF REPRODUCTIVE HEALTH INFORMATION TOWARDS ADOLESCENT SEXUAL BEHAVIOR - Bernadeta Verawati; Kenik SW (Universitas Andalas, 2020)
range of 10 to 19 years. Adolescents are the population in the age range of 10-18 years. Rapid physical changes and hormonal changes are triggers for sexual motivation. Stimulation from the environment such as TV and the internet about sexual behavior and nutritional factors causes sexual hormones to appear earlier so that adolescents tend to experience sexual development more quickly. The rise of adolescent sexual behavior at this time is increasingly concerning and tends to increase both in terms of the quantity and sharpness of cases that occur.Method: This type of research is an observational analytic with a cross-sectional study design, to analyze the exposure to reproductive health information on adolescent sexual behavior in Sleman Regency. Samples were taken from adolescents who were in class XI SMAN 2 Ngaglik with a purposive sampling technique of 198 students. Data collection using a questionnaire via google form. Data were analyzed using univariate, bivariate, and multivariate analyzes.Results: There is a relationship between reproductive health information from parents with adolescent sexual behavior (P value 0.00), there is a relationship between information from peers and adolescent sexual behavior (P value 0.00), there is a relationship between media access and adolescent sexual behavior ( P value 0.06) Adjusted RSquare value = 0.541.Conclusion: Of the three variables, information from parents and from peers has the same relationship with sexual behavior in adolescents, and media access is smaller than the other two variables.